Downregulation of miR-211-5p Promotes Carboplatin Resistance in Human Retinoblastoma Y79 Cells by Affecting the GDNF–LIF Interaction - Ke, Ning; Chen, Lin; Liu, Qing; Xiong, Haibo; Chen, Xinke; Zhou, Xiyuan (Frontiers in Oncology, 2022)
More effort is needed to clarify the molecular mechanisms and signal pathways closely related to the carboplatin resistance of retinoblastoma. To elucidate the mechanism of chemoresistance in retinoblastoma(RB), we explored miR-211-5p-GDNF signaling pathway in the carboplatin resistance mechanism of RB and what factors it may be affected by. A carboplatin resistant retinoblastoma cell line (Y79R) was established in in vitro. RNA-seq and microRNA-seq were constructed between Y79 and Y79R cells. Small RNA interference was used to verify whether the expression of GNDF affects Y79 cell lines. RT-PCR, western blot(WB) and flow cytometry were used to analyze the gene and protein expression of GNDF between the two cell lines. TargetScanHuman version 7.1 was used to analyze the GDNF binding target microRNA. STING web site and Co-Immunoprecipitation (COIP) were used to investigate protein-protein interaction. GDNF was speculated to be the top changed gene in the drug resistance in Y79R cell lines. And the speculation was verified by subsequent RT-PCR and WB results. When the expression of GDNF was knocked down, the IC50 of the Y79R cell line significantly reduced. GDNF was found to be the target gene of miR-211-5p. Downregulation of miR-211-5p promotes carboplatin resistance in human retinoblastoma Y79 cells. MiR-211-5p can egulate the expression of GDNF. Our further research also found that GDNF can bind to LIF which is also a secreted protein. Our results suggest that downregulation of miR-211-5p promotes carboplatin resistance in human retinoblastoma Y79 cells , and this process can be affected by GDNF-LIF interaction. These results can provide evidence for the reversal of drug resistance of RB.